Design and optimisation of XAM 2.0 plug-in powertrain. Issue 3 (2017) - Ferraris, A.; Xu, S.; Airale, A.G.; Carello, M.
After the European Union Legislation set mandatory emission and consumption standards for 2020, an upgrade for personal mobility in cities has become a priority in the automotive sector. Electrification of the existing traditional car platforms while facing problems like weight repartition, battery cost and the weight to maintain the same performances is not feasible in a short period. In this paper, a case study of developing a hybrid powertrain is presented with systematic designing phase, system dimensioning and selection of the different subsystems for XAM 2.0, an innovative prototype city vehicle designed at the Politecnico di Torino. Thanks to these solutions, XAM 2.0 won the first prize for the 'Best Range Extender Prototype' at the Brighton-London Future Car Challenge 2012, running with different OEMs and car-makers.